TINJAUAN TRADISI BUWUHAN PERNIKAHAN DALAM PERSPEKTIF HUKUM ISLAM (DI DESA BENDET KECAMATAN DIWEK KABUPATEN JOMBANG) - M. Wildan Jumanuba; Ahmad Ubaidi Hasbillah (JOURNAL SAINS STUDENT RESEARCH, 2024)
The buwuhan tradition in Bendet Village, Diwek District, Jombang Regency, as described, involves the act of donating items with an expectation of reciprocity. This tradition is rooted in strengthening Islamic brotherhood (ukhuwwah) through mutual assistance. The research employs a phenomenological approach to describe and analyze this tradition qualitatively, focusing on observing and documenting the interactions surrounding buwuhan. It concludes that requesting the return of donated items, if not reciprocated appropriately, is considered permissible under Islamic law, given the community's expectation of reciprocity in their giving.